Radioprotective Effect of Arbutin in Megavoltage Therapeutic X-irradiated Mice using Liver Enzymes Assessment - S Nadi; M Elahi; S Moradi; A Banaei; Gh Ataei; R Abedi Firouzjah (Journal of Biomedical Physics and Engineering, 2019)
Background: Medical use of ionizing radiation has direct/indirect undesirable effects on normal tissues. In this study, the radioprotective effect of arbutin in megavoltage therapeutic x-irradiated mice was investigated using serum alkaline phosphatase (ALP), alanine aminotransferase (ALT), and asparate amniotransferase (AST) activity measurements. Material and Methods: In this analytical and experimental lab study, sixty mice (12 identical groups) were irradiated with 6 MV x-ray beam (2 and 4 Gy in one fraction). Arbutin concentrations were chosen 50, 100, and 200 mg/kg and injected intraperitoneal 2 hours before irradiation. Samples of peripheral blood cells were collected and serum was separated on the 1, 3, and 7 days post-x-radiation; in addition, the level of ALP, ALT, and AST were measured. Data were analyzed using one-way ANOVA, and Tukey HSD test. Results: X-radiation (2 and 4 Gy) increased the ALT and AST activity levels on the 1, 3, and 7 days post- irradiation, but the ALP level significantly increased on the 1 and 7 days and decreased on the third day compared to the control group (P< 0.001). ALP, ALT and AST activity levels in “2 and 4 Gy x irradiation + distilled water” groups were significantly higher than “2 and 4 Gy irradiation + 50, 100, and 200 mg/kg arbutin” groups on the first and seventh day post-irradiation (P< 0.001). Conclusion: Arbutin is a strong radioprotector for reducing the radiation effect on the whole-body tissues by measuring ALP, ALT and AST enzyme activity levels. Furthermore, the concentration of 50 mg/kg arbutin showed higher radioprotective effect.